Structural characterization and partial properties of dextran produced by Leuconostoc mesenteroides RSG7 from pepino - Wang, Binbin; Sun, Xiaoling; Xu, Min; Wang, Fengyi; Liu, Weizhong; Wu, Baomei (Frontiers in Microbiology, 2023)
Exopolysaccharides (EPSs) produced by lactic acid bacteria possess various bioactivities and potential attractions for scientific exploration and commercial development. An EPS-producing bacterial strain, RSG7, was previously isolated from the pepino and identified as Leuconostoc mesenteroides. Based on the analyses of high performance size exclusion chromatography, high performance ion chromatography, fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy and methylation, the RSG7 EPS was identified as a dextran with molecular weight of 5.47×106 Da and consisted of α-(1→6) glycosidic linkages as backbone and α-(1→2), α-(1→3), α-(1→4), α-(1→6) glycosidic linkages as side chains. Scanning electron microscopy observed a honeycomb-like porous structure of RSG7 dextran, and this dextran formed aggregations with irregular hill shaped lumps according to atomic force microscopy analysis. Physical-chemical investigations suggested that RSG7 dextran possessed excellent viscosity at high concentration, low temperature and high pH, showed superior emulsifying capacity of tested vegetable oils than that of hydrocarbons, and owned the maximal flocculating activity (10.74±0.23) and flocculating rate (93.46±0.07%) in the suspended solid of activated carbon. Additionally, the dextran could coagulate sucrose-supplemented milk and implied potential probiotics in vitro. Together, these results collectively describe a valuable dextran with unique characteristics for exploitation in food applications.